PENGARUH LIKUIDITAS DAN RISIKO KREDIT TERHADAP KINERJA KEUANGAN PERBANKAN : STUDI KASUS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Purnama, Ni Wayan Dinda; Dewi, Putu Pande R. Aprilyani; Ariwangsa, I Gusti Ngurah Oka; Widiantari, Komang Sri (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The COVID-19 pandemic has had a significant impact on various economic sectors, including the banking industry. In the aftermath of the pandemic, Indonesia's banking segment experienced changes in its financial performance, as reflected in indicators such as liquidity, profitability, and credit risk. These changes were influenced by economic policies implemented by the government during the pandemic, such as credit restructuring and reductions in benchmark interest rates. According to data from the Financial Services Authority (Otoritas Jasa Keuangan, OJK) at the end of 2021, the non-performing loan (NPL) ratio in Indonesian banks increased to 5.24%, compared to 2.49% before the pandemic, as a result of elevated credit risks due to customers' inability to meet their obligations. While the post-pandemic financial performance of the banking sector has shown signs of recovery, challenges such as rising credit risk and liquidity fluctuations remain, making liquidity improvement and profitability enhancement key focuses for ensuring future stability and positive performance in Indonesia's banking sector. This study aims to analyze and understand how liquidity and credit risk affect financial performance. Annual financial reports serve as secondary data for this study, with a sample of 97 banking companies’ data from 2021 to 2023. Data analysis employs multiple linear regression techniques. The findings reveal that liquidity has a positive and significant effect on financial performance. Furthermore, credit risk also demonstrates a positive and significant correlation with financial performance. Simultaneously, liquidity and credit risk significantly influence financial performance